A Political Approach to Organizations: A Review and Rationale - Tushman, Michael L. (Academy of Management Review, 1977)
In ignoring the implications of systems thinking at the intra-organizational level of analysis, organizational literature has obscured the fact that organizational behavior (OB) occurs as a result of subunit dynamics within the organization. Several assumptions are basic to a political approach to OB. Organizational development literature is discussed from a political perspective.